Conjoint measurement underdone: Comment on Günter Trendler (2019). (February 2019) - Michell, Joel
Trendler's (2019) critique of conjoint measurement fails because he neglects to distinguish standard sequences (human constructions) from series of equal magnitudes (features of quantitative structures). The latter, not the former, is presumed in conjoint measurement. Furthermore, in so far as some mental tests use humans as measuring instruments, the only questionable assumption involved is that the relevant psychological attributes are quantitative, and that assumption is potentially testable using conjoint measurement. Finally, contrary to Trendler, psychological phenomena can be captured and the structure of psychological attributes investigated using conjoint measurement.